2020
DOI: 10.1111/1346-8138.15533
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab in Japanese patients with active ulcers of pyoderma gangrenosum: Twenty‐six‐week phase 3 open‐label study

Abstract: This phase 3 multicenter study, including 26-week treatment and extension periods, evaluated the efficacy and safety of adalimumab in Japanese patients with active ulcers due to pyoderma gangrenosum. Patients received adalimumab 160 mg at week 0, 80 mg at week 2, and then 40 mg every week starting at week 4. Of the 22 enrolled patients, 12 (54.5%, P < 0.001) achieved the primary efficacy end-point of pyoderma gangrenosum area reduction 100 (PGAR 100, defined as complete skin re-epithelialization) for the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 17 publications
2
43
0
Order By: Relevance
“…Although the role of cytokines in pathogenesis of PG is not fully understood, overexpression of tumor necrosis factor alpha (TNFα) is associated with the neutrophil infiltration characteristic of PG; therefore, this group of drugs may be useful. A multicenter study evaluated the efficacy and safety of adalimumab in active ulcers of PG [ 46 ]. In this clinical trial, 22 enrolled patients received adalimumab 160 mg at week 0, followed by 80 mg at week 2, and then 40 mg every week starting at week 4.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Although the role of cytokines in pathogenesis of PG is not fully understood, overexpression of tumor necrosis factor alpha (TNFα) is associated with the neutrophil infiltration characteristic of PG; therefore, this group of drugs may be useful. A multicenter study evaluated the efficacy and safety of adalimumab in active ulcers of PG [ 46 ]. In this clinical trial, 22 enrolled patients received adalimumab 160 mg at week 0, followed by 80 mg at week 2, and then 40 mg every week starting at week 4.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…To address the need for alternative medication for refractory PG, we carried out a phase 3 randomized open‐label study to evaluate the efficacy, safety, and pharmacokinetics of adalimumab 40 mg every week for 52 weeks in Japanese patients with active ulcers of PG. Analysis at 26 weeks showed that the primary endpoint of PG area reduction 100 (PGAR 100, defined as complete skin re‐epithelialization) in the target ulcer was achieved by 12 of the 22 participants (54.5%) 16 . Findings from this interim analysis supported the approval of adalimumab (Humira®) for the treatment of PG in Japan in November 2020.…”
Section: Introductionmentioning
confidence: 66%
“…Eligibility criteria for the study have been reported previously 16 . In brief, patients ≥18 years old, diagnosed by the investigator as having active ulcerative (classic) PG (including peristomal PG), and who had an inadequate response to or were not candidates for topical PG therapy, were eligible for inclusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate-dose systemic corticosteroid has long been used for the treatment of PG. However, because of several adverse effects [ 1 , 9 ], adalimumab was adopted as a treatment owing to its effectiveness and safety compared to oral corticosteroid with regard to the healing speed of intractable ulcer [ 10 , 11 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%